MUSEUM IS A MIRROR OF THE HISTORY (Scientific journal of the Fergana State University, 2023)
The article presents brodd information about the museum “Memory of Victims of Repression” which is situated in the structure of Fergana state University. The history of the main building where the museum is situated is exposed.